3-(+2)-(+33)+(-18)-(-27)
gente me ajuda por favor​


Resposta :

3-(+2)=1

+1-33= -32

-32+(-18)= -50

-50-(-27)=-23

resposta final é -23

-23

-(+2) = - 2

-(+33)= - 33

+(-18) = - 18                                      

-(-27)= +27

                                        = (3-2)(-33-18)+27

                                        = 1 - 51 + 27

                                         = -50 + 27

                                         = -23

Saiba mais em:

https://brainly.com.br/tarefa/1412377

Ver imagem VINICIUSCOUTINHO90